ENVIRONMENTAL FUNCTION OF PROPERTY: A CONCEPTUAL PROPOSAL - Araújo, Giselle Marques de (Veredas do Direito, 2023)
The article intends to deeply examine the substance of the expression œenvironmental function of the private property, verifying if the environmental function is a species of the genre œsocial function and the relevance of the frequent usage of the term œsocial environmental function of property. To accomplish that, it inserts the theme in the context of the General Theory of Fundamental Rights, understanding right to property and right to a balanced environment as rights historically conquered and modified. Brings to the center of the analysis hypothesis in which the social and environmental interests collide, such as the need of settlement for landless families in environmentally sensitive areas. In search for an explaining principle, the research uses the Inductive-Deductive Method proposed by Aristotle, arriving in the conclusion that, even though the social and environmental function of property share a common foundation, they both share different substances, the first directed towards the protection and defense of the environment, and the second to the generation of resources (employment and income) and food production. Therefore, the usage of the expression œsocial-environmental function of property is not always adequate. Regarding the conceptual aspect, defends œthe environmental function of property as an output or fulfillment of the purpose of environmental conservation, and as a category that carries value within itself.